The Time-Space Joint Response Characteristics of AE-UT under Step Loading and Its Application - Xiaoran Wang; Xiaofei Liu; Enyuan Wang; Chong Zhang; Haishan Jia; Dexing Li (Shock and Vibration)
The acoustic emission (AE) and ultrasonic (UT) simultaneous monitoring program is designed using concrete samples under step loading. The time-varying response characteristics of AE-UT are studied and the cross-correlation analysis between AE-UT parameters is obtained. Moreover, the joint response of UT-AE spatial distribution field is analyzed, and an AE-UT joint monitoring method to detect early-warning signals of a rockburst disaster in a coal seam is proposed. The results show the following. (1) During the loading process, the AE pulses/energy and UT attenuation coefficient first slowly decrease and then increase steadily and finally rapidly increase, while the UT velocity shows a trend of first gradually increasing and then slowly decreasing and finally a sharp decline. (2) AE pulses and energy are significantly or highly correlated with the UT velocity and attenuation coefficient. The AE energy and UT attenuation coefficient can better characterize the damage evolution of concrete under step loading. (3) The UT field evolves ahead of the rupture on the surface, and the long/narrow strip distribution region of UT parameters is consistent with the future failure zone; meanwhile, the AE events can visually reflect the evolution path of internal damage as well as the dynamic migration mechanism of UT field.